PENGARUH SUPERVISI AKADEMIK DAN PELATIHAN PENELITIAN TINDAKAN KELAS TERHADAP KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR SE-KECAMATAN UNDAAN KABUPATEN KUDUS - Aribowo, A.; Su'ad, S.; Madjdi, Achmad Hilal (Universitas Muria Kudus, 2020)
The purpose of this study is 1) to know effect of academic supervision on the professional competencies of elementary school teacher, 2) to know the effect of classroom action research training on the professional competencies of elementary school teachers, 3) to know effect of academic supervision and classrooom action research training on the professional competencies of elementary school teacher. The subject of this study werw all elementary school teachers in all subdistrict of Undaan Kudus regency. This study uses a quantitative contribution method with regression analysis techniques. Respondents were selected using a purposive sampling technique. Data collection research using questionaire. The validity of data uses construct validity bay way of experiential juggment. Data analysis was perfomed using regression analysis techniques in the form of simple and multiple regression. The results of study showed that academic supervision had an effect on techer professional competence of 32,0 %. Whereas classroom action research training has an effect onÂ teacher professional competence of 39,1%. Academic supervision and classroom action research training together have an effect on teacher professional competence of 46,6%.